Do new anticancer drugs really work? A serious concern - Bizzarri, Mariano (Organisms. Journal of Biological Sciences, 2017)
Commentary on: Wise PH , 2016, Cancer Drugs, Survival, Ethics, BMJ, vol. 355, pag. 1-3. Godlee F., 2016, Too much chemotherapy, BMJ, vol. 355 (Editorial).